Building sensor networks : from design to applications - Nikolaidis, I. (Ioanis); Iniewski, Krzysztof, 1960- (Boca Raton, [Florida] : CRC Press, 2014)
'The book contains contributions that draw from experiences from developments in the state-of-the-art of wireless sensor network enabling technologies, as well as from existing applications and services built on wireless sensor technologies, leveraging also knowledge from applications that operate using existing technologies but are expected to become more flexible with the ubiquitous deployment of wireless sensor networks'--
Includes bibliographical references and index.
Keywords: Sensor networks -- Design and construction; Wireless communication systems -- Design and construction